The Epidemiology of Pulmonary Nontuberculous Mycobacteria: Data from a General Hospital in Athens, Greece, 2007–2013 - Marios Panagiotou; Andriana I. Papaioannou; Konstantinos Kostikas; Maria Paraskeua; Ekaterini Velentza; Maria Kanellopoulou; Vasiliki Filaditaki; Napoleon Karagiannidis (Pulmonary Medicine)
Background. The epidemiology of pulmonary nontuberculous mycobacteria (NTM) in Greece is largely unknown. Objectives. To determine the incidence and the demographic, microbiological, and clinical characteristics of patients with pulmonary NTM infection and pulmonary NTM disease. Methods. A retrospective review of the demographic, microbiological, and clinical characteristics of patients with NTM culture-positive respiratory specimens from January 2007 to May 2013. Results. A total of 120 patients were identified with at least one respiratory NTM isolate and 56 patients (46%) fulfilled the microbiological ATS/IDSA criteria for NTM disease. Of patients with adequate data, 16% fulfilled the complete ATS/IDSA criteria for NTM disease. The incidence of pulmonary NTM infection and disease was 18.9 and 8.8 per 100.000 inpatients and outpatients, respectively. The spectrum of NTM species was high (13 species) and predominated by M. avium-intracellulare complex (M. avium (13%), M. intracellulare (10%)), M. gordonae (14%), and M. fortuitum (12%). The ratio of isolation of NTM to M. tuberculosis in all hospitalized patients was 0.59. Conclusions. The first data on the epidemiology of pulmonary NTM in Athens, Greece, are presented. NTM infection is common in patients with chronic respiratory disease. However, only a significantly smaller proportion of patients fulfill the criteria for NTM disease.